The Determinants of Money-Laundering Behavior in Indonesia - Vita Fauziah Ningtyas; Munawar Ismail; Setyo Wahyudi (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
Banks nowadays have come with innovations in all of their operations, particularly in account application. Therefore, people can apply for their account personally from any places by using the smartphone technology. However, it increases the possible risk of money laundering, especially in banking. One of the phenomena is the high number of Suspicious Financial Transaction Reports (LTKM) received by the Financial Transaction Reports and Analysis Center (INTRAC). Hence, this study analyzes the effect of Indonesia’s social demography on the risk of each individual of committing money laundering.Using secondary data obtained from INTRAC, the derived and selected independent variables was analyzed using ordinal logistic regression to determine their effect on the dependent variable, i.e. the Money Laundering Risk Score (MLRS). This study finds that the social demographic factors affecting the risk of money laundering committed by individuals are sex, age, marital status, occupation, and the history of financial service usage, in which occupation has the highest effect.